Magnetic resonance imaging of infarct-induced canonical wingless/integrated (Wnt)/β-catenin/T-cell factor pathway activation, in vivo. Issue 3 (26th September 2016) - Matteucci, Marco; Casieri, Valentina; Gabisonia, Khatia; Aquaro, Giovanni Donato; Agostini, Silvia; Pollio, Giuseppe; Diamanti, Daniela; Rossi, Marco; Travagli, Massimiliano; Porcari, Valentina; Recchia, Fabio A.; Lionetti, Vincenzo
Abstract : Aims: Combined magnetic resonance imaging (MRI) of molecular and morpho-functional changes might prove highly valuable for the elucidation of pathological processes involved in the development of cardiac diseases. Our aim was to test a novel MRI reporter gene for in vivo assessment of the canonical Wnt/β-catenin/TCF pathway activation, an important regulator of post-ischaemic cardiac remodelling. Methods and results: We designed and developed a chimeric construct encoding for both of iron-binding human ferritin heavy chain (hFTH) controlled by the β-catenin-responsive TCF/lymphoid-enhancer binding factor (Lef) promoter and constitutively expressed green fluorescent protein (GFP). It was carried by adeno-associated virus serotype 9 (rAAV9) vectors and delivered to the peri-infarct myocardium of rats subjected to coronary ligation ( n = 11). By 1.5 T MRI and a multiecho T2* gradient echo sequence, we detected iron accumulation only in the border zone of the transduced infarcted hearts. In the same cardiac area, post-mortem histological analysis confirmed the co-existence of iron accumulation and GFP. The iron signal was absent when rats ( n = 6) were chronically treated with SEN195 (10 mg/kg/day), a small-molecular inhibitor of β-catenin/TCF-dependent gene transcription. Canonical Wnt pathway inhibition attenuated the post-ischaemic remodelling process, as demonstrated by the significant preservation of cardiac function, the 42 ± 1% increase of peri-infarct arteriolar density and 43 ± 3% reduction in infarct scar size compared with untreated animals. Conclusions: The TCF/Lef promoter-hFTH construct is a novel and reliable MRI reporter gene for in vivo detection of the canonical Wnt/β-catenin/TCF activation state in response to cardiac injury and therapeutic interventions.